Development of an Active Learning-Based Biology KIT for Class XI MIA Students on Digestive System Material - Clarisa Ayu Aprilia; Muhamad Jalil (Bioeducation Journal, 2023)
The digestive system is one of the materials in class XI MIA which requires students to be able to present a report on the results of the food test practicum. However, in Biology learning at MA Ihyaul Ulum this has not been realized. This is due to the unavailability of laboratories and supporting tools and materials for practicum, as well as the lack of innovation from teachers. When teaching Biology, teachers tend to use the lecture method so that students become less active in learning Biology. Therefore, a learning media was developed that can be used to conduct a food test practicum on digestive system material in the form of an Active Learning-Based Biology KIT. This study aims to develop and test the validity and practicality of the Biology KIT products developed. This research uses the 4-D development model which is simplified into 3-D. This research was conducted at MA Ihyaul Ulum Wedarijaksa Pati on 6 February 2023 to 6 March 2023 with the subject of Class XI MIA 1 which numbered 33 students. This study found that the Active Learning-Based Biology Learning KIT product developed in the category of highly valid with a percentage score of 95% based on the assessment of material experts and a score of 98% based on the assessment of media experts. In addition, the Active Learning-Based Biology Learning KIT product developed is also in the very practical category with a score of 96% based on teacher trials and 93% based on student trials.